2022
DOI: 10.3389/fpsyg.2021.762499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Top Management Team Characteristics on Patent Strategic Change and Firm Performance

Abstract: Patent strategy is increasingly recognized as a vital contributor in promoting core competitiveness of an enterprise. A top management team (TMT) has been indicated as one of the key factors driving changes in patent strategy. Based on upper echelons theory, this study examines how TMT characteristics, including, team diversity, emotional intelligence, and safety climate, influence enterprise patent strategic change and, hence, the business outcome. The data from 930 top managers in 228 enterprises showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Our main results show that executive overconfidence had a significant positive effect on environmental technology innovation; however, it had no significant effect on environmental management innovation. This result further supports the research of He et al [8] and Zhou et al [35], suggesting that executives' experience (e.g., academic experience) and personal traits (e.g., age and gender) can significantly influence their cognitive and psychological characteristics, thus, affecting environmental innovation. However, according to Ren et al [1], the uncertainty and risk of environmental management innovation are relatively lower compared with those of environmental technology innovation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our main results show that executive overconfidence had a significant positive effect on environmental technology innovation; however, it had no significant effect on environmental management innovation. This result further supports the research of He et al [8] and Zhou et al [35], suggesting that executives' experience (e.g., academic experience) and personal traits (e.g., age and gender) can significantly influence their cognitive and psychological characteristics, thus, affecting environmental innovation. However, according to Ren et al [1], the uncertainty and risk of environmental management innovation are relatively lower compared with those of environmental technology innovation.…”
Section: Discussionsupporting
confidence: 90%
“…The extant literature documents that executives' backgrounds, personal attributes, and leadership styles have profound impacts on the organizational strategy and effectiveness [12,33]. For instance, the prominent characteristics of CEOs, such as age, gender, educational background, professional experience, and financial position, are appropriate proxies of psychological and behavioral traits, which further affect the output results [34,35]. Among these characteristics, executive overconfidence, as a typical psychological personality, has been proven to be crucial for innovation activities [12,36].…”
Section: Executive Overconfidence and Environmental Innovationmentioning
confidence: 99%
“…Based on upper echelons theory, the heterogeneity of top management team characteristics has been highlighted as an important factor affecting the long-term operation of enterprises [ 23 ]. Such heterogeneity refers to team members’ individual backgrounds—specifically, differences in age, tenure, education level, and other backgrounds [ 24 ]. The influence of background heterogeneity has been conceptualized differently under different theoretical frameworks.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Specifically, some researchers have demonstrated that top management teams with a diverse knowledge base and career experience can more effectively make decisions in dynamic and changing environments and are more creative and able to solve specific problems, therefore improving innovation performance [ 26 ]. This is because the existence of heterogeneity means that members of the top management team can access different information sources and divergent views on the basis of differentiated cognition to solve problems, which is conducive to enterprise learning and performance improvement [ 24 , 27 ]. Other scholars have applied social identity theory to argue that individuals tend to associate more with those who are similar to them, such that heterogeneity will affect top management team members’ identity; inhibit the transfer of professional skills within the team [ 28 , 29 ]; increase the likelihood of conflicts; and produce greater differences in the process of formulating strategies, strategic objectives, and strategic plans [ 30 , 31 ].…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…The authors also argue that strategic choices and performance levels are partially predicted by managerial background characteristics such as age, education, socioeconomic background, financial position, gender, and group heterogeneity. Henceforth, the literature has focused more on the impacts of top management characteristics on firm policy choices with convincing evidence ( Bertrand and Schoar, 2003 ; Bamber et al, 2010 ; Graham et al, 2013 ; Jiang et al, 2022 ; Zhou et al, 2022 ). Research in top management has identified TMTs as the primary driver of a firm’s strategic decision-making ( Papadakis and Barwise, 2002 ; Hambrick, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%